Avaliação na política pública Areninha de Fortaleza: uma análise esportiva do entorno da Areninha do Campo do América - Oliveira, Túlio César Pinheiro de (2024)
This study aimed to evaluate the implementation of the Areninha policy within the scope of the Fortaleza Municipal Government, focusing on its social, sporting, and economic impacts on its surroundings. Such evaluation was analyzed according to the counter-hegemonic evaluative proposal developed by Rodrigues (2008), seeking a more extensive assessment to understand the said policy from various aspects, including its constitution and the perception of the involved actors. To this end, an analysis was developed along three axes: content, context, and trajectory. This evaluation aimed to adopt a qualitative approach, seeking to understand the impact of the Areninha public policy in Fortaleza in the context of social inclusion through sports. For the proposition of this evaluation, bibliographic and documentary research, legal texts, and published materials related to the Areninha public policy were sought to gather sufficient information for understanding this policy. Among these studies, concepts and theories from, among others, Bourdieu and Norbert Elias were presented regarding the influence of sports on an individual's social position. Data and information were collected through in-depth interviews with the main actors involved in the Areninha public policy, conducted in person, aiming to comprehend the central objectives of the project, whether they were effectively developed, and the main changes carried out in the vicinity of the facility. Thus, it was concluded that the Areninha public policy promotes social inclusion and access to sports, contributing to social regulation and positively impacting the local community. However, the absence of legal instruments that enable the definition of guidelines and objectives for the program was also observed. Finally, it is concluded that there is a need for the instrumentalization of the Areninha public policy through normative instruments that regulate the use, installation, maintenance, and other processes affecting the policy, to prevent it from serving as a political instrument and being controlled by individuals with personal interests.